Postharvest Pathology - Prusky, Dov.; Gullino, Maria Lodovica; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2010)
As a collection of papers that includes material presented at the 2008 International Congress for Plant Pathology, this text features research right at the leading edge of the field. The latest findings are particularly crucial in their implications for fruit production; an important market sector where in some areas up to 50 per cent of the crop can be lost after harvest. While post-harvest fruit treatments with fungicides are the most effective means to reduce decay, rising concerns about toxicity have led to the development of alternative approaches to disease control, including biological methods, the subject of three chapters of this book. With several new techniques requiring modification of current post-harvest practices, it is more important than ever to stay abreast of the latest information. Other chapters deal with the mechanisms of host fruit and vegetable resistance, fungal pathogenicity factors and their relationship with the host response, and a number of subjects related to disease assessments before harvest as well as their relationship to the postharvest treatment of fruits and vegetables. The book also includes several useful case studies of crops such as kiwifruit and peaches, where different approaches at the pre- and post-harvest levels are combined to good effect. With food production issues gaining an ever higher profile internationally, this text makes an important contribution to the debate.
The Role of Pre-formed Antifungal Substances in the Resistance of Fruits to Postharvest Pathogens -- Mechanisms of Induced Resistance Against B. cinerea -- Induced Resistance in Melons by Elicitors for the Control of Postharvest Diseases -- Mechanisms Modulating Postharvest Pathogen Colonization of Decaying Fruits -- Global Regulation of Genes in Citrus Fruit in Response to the Postharvest Pathogen Penicillium digitatum -- Epidemiological Assessments and Postharvest Disease Incidence -- Preharvest Strategies to Control Postharvest Diseases in Fruits -- New Developments in Postharvest Fungicide Registrations for Edible Horticultural Crops and Use Strategies in the United States -- New Approaches for Postharvest Disease Control in Europe -- Quo Vadis of Biological Control of Postharvest Diseases -- Improving Formulation of Biocontrol Agents Manipulating Production Process -- Host Responses to Biological Control Agents -- Non-fungicidal Control of Botrytis Storage Rot in New Zealand Kiwifruit Through Pre- and Postharvest Crop Management -- The Peach Story.
Keywords: Life sciences; Agriculture; Bioinformatics; Botany; Plant diseases; Life Sciences; Plant Pathology; Plant Sciences; Agriculture; Bioinformatics